CHINESE IMMIGRATION AND ITS IMPLICATIONS ON URBAN MANAGEMENT IN LOS ANGELES - CHEN, Xueming (Theoretical and Empirical Researches in Urban Management, 2009)
This paper reviews the Chinese immigration history in Los Angeles, with Chinatown representing its urbanization process and San Gabriel Valley representing its suburbanization process. These two processes are distinct and have different impacting factors. This empirical study also compares similarities and differences of the urban development patterns between the Chinese Americans and the mainstream white Americans. Furthermore, the paper examines the implications of Chinese immigration on local urban management from political, cultural, and socioeconomic aspects.